Humanism Reformed: Narrative and the Divine-Human Encounter in Paul Ricoeur - Whitehouse, Glenn (Religions, 2022)
"Narrative Theology" has often been construed in contrast to broader humanistic discourse. Protestant and particularly Reformed Christianity has often set the "Old, Old Story" apart from humanism and the humanities. This chapter explores the juxtaposition of humanism and reformed thinking in Paul Ricoeur. Ricoeur’s hermeneutics is compared with the Reformed "covenant theology" of 17th Century Puritanism. Covenant theology balanced the belief that God exceeds our powers of knowing and language and the conviction that God consents to be known within the limits of human understanding, as developed through the liberal arts. Similarly, Ricoeur sees God as limiting and disrupting human language, but while, for Ricoeur, encounter with God may begin as impossible dialogue, it develops by dispersing the names and signs of the divine throughout the tropes and genres of human discourse, narrative chief among them. Ricoeur’s thought is interpreted as a Christian humanism in which religious inquiry and secular humanistic thought coexist and mutually enhance one another. Ricoeur’s humanism will be preferred over approaches to narrative that set the Christian story and its hearers apart from the broader conversation of culture; a solipsism of faith is inadequate to the challenges of a modern pluralist culture.